How Customer Loyalty Model Be Operative? A study of Cellular Phone Service Providers in Pakistan - Junaid-ul-haq, Junaid-ul-haq; ., Rao Umer Nasir (Information Management and Business Review, 2013)
The idea of this study is raised because of tough competition in cell phone industry of Pakistan. In this scenario, every organization after retaining customer tries to make him/her loyal. The loyalty, which has rigorously investigated, empirically tested with different combination of variables, which collectively help in making the customer loyal. Data were collected through 508 questionnaires. Respondents were pre-paid cell phone customers. Data was analyzed via factor loading and reliability of variables. Structural Equation Modeling (SEM) technique was used for the testing of hypotheses. Loyalty model was found significantly responsive for cellular phone services in Pakistan. Perceived service quality, satisfaction, trust and image have chained link of positive affects, which leads to loyalty of customers in the telecom sector of Pakistan. Customers do not take effect of perceived service quality. However, it is service quality, which satisfies customer through image of the organization. This loyalty model is more preferably applicable in the industry where competition is tough and switching rate is high. In future researches, this model can be tested across the culture. Moreover, more variables can be added to strengthen the loyalty model.